Weed Management in Rice under Sprinkler and Flood Irrigation Systems - HELGUEIRA,D.B. (2018)
ABSTRACT: This study aimed to assess the efficiency and selectivity of herbicides in rice submitted to sprinkler and flood irrigation systems. The experimental design was a randomized block design arranged in a 2 × 9 factorial scheme. Factor A consisted of irrigation systems (sprinkler and flood) and Factor B consisted of herbicide treatments (T1 - control; T2 - imazethapyr + imazapic, 75 + 25 g a.i. ha-1; T3 - imazethapyr + imazapic, 150 + 50 g a.i. ha-1; T4 - imazapic + imazapyr, 73.5 + 24.5 g a.i. ha-1; T5 - imazapic + imazapyr, 147 + 49 g a.i. ha-1; T6 - imazethapyr, 106 g a.i. ha-1; T7 - imazethapyr, 212 g a.i. ha-1; T8 - sequential application of imazethapyr + imazapic, 75 + 25 g a.i. ha-1; and T9 - sequential application of imazapic + imazapyr, 73.5 + 24.5 g a.i. ha-1). The application of imazethapyr and formulated mixtures of imazethapyr + imazapic and imazapyr + imazapic provided a control higher than 97% in flood and sprinkler irrigation systems. Herbicide selectivity is not altered in the sprinkler irrigation system when compared to the flood irrigation system.